The Influence of “English Fairy Tales” Youtube Channel on Students’ Listening Comprehension Ability - Faridah, Fita; Kusumaningtiyas, Kusumaningtiyas; Fatmawaty , Riryn; Anam , Mukhtarul (The Future of Education Journal, 2025)
This study investigates the impact of the “English Fairy Tales” YouTube channel on students’ listening comprehension abilities in an EFL context. Listening comprehension is a crucial yet often neglected skill among Indonesian EFL learners, who struggle due to limited exposure to authentic spoken English and lack of engaging instructional materials. To address this issue, the study examines whether digital storytelling specifically, fairy tales on YouTube can enhance students' listening skills. The study used a quantitative, quasi-experimental design with a pretest-posttest control group. A total of 70 tenth-grade students from SMA Negeri 1 Sukodadi were divided into experimental and control groups. Data were collected using multiple-choice listening tests and analyzed using t-tests and effect size measurement. The findings revealed a significant improvement in the experimental group’s post-test scores (from 51.57 to 67.14), while the control group’s scores declined (from 48.43 to 44.00). Statistical analysis confirmed a significant difference between groups (p < 0.001). These results suggest that storytelling videos from the “English Fairy Tales” YouTube channel effectively improve students’ listening comprehension. The study concludes that integrating digital storytelling into EFL instruction offers a valuable, engaging approach to overcoming traditional listening barriers and should be considered in modern language classrooms.